Harmonizing The Distribution of Inheritance Property in Inter-Religious Families - Christofel Hutagaol, Daniel Hotma; Basani, Christin Septina (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study explores the harmonization of inheritance laws in interfaith families, specifically addressing the distribution of inherited assets among members with different religions. It focuses on the application and distribution of inheritance laws for interfaith families, referring to Law Number 1 of 1974 concerning Marriage and Supreme Court Circular Letter Number 2 of 2023 concerning Guidelines for Judges in Adjudicating Cases of Registration of Marriages between Believers of Different Religions and Beliefs.  Applying a legal normative method, the findings conclude that there are three systems of inheritance laws in Indonesia: civil law, Islamic inheritance law, and customary law.  The resolution of inheritance distribution in interfaith families within in Islam involves the application of "wasiat wajibah," while for non-Muslim faiths (Hindu, Christian, Catholic, Buddhist, Confucian), civil law or customary law adhered to by the deceased applies.  Inheritance law issues in interfaith families in Indonesia necessitates a specific regulation to minimize legal uncertainty and confusion in the distribution of inheritance among interfaith families